Creating a body-subject in the Late Moche Period (CE 650 - 850). Bioarchaeological and biogeochemical analyses of human offerings from Huaca Colorada, Jequetepeque Valley, Peru - Alaica, Aleksa K.; González La Rosa, Luis Manuel; Knudson, Kelly J. (World archaeology, 2020)
Human offerings in the archaeological record are commonly defined by their community affiliation, the ceremonial events following their death and the places where they are interred. The deposition of an individual links kin members to the landscape but also seems to mark time and memory. Here we argue that inter-generational memory, created through cyclical depositions of local, coastal community members at Huaca Colorada, reflects political alliances during the Late Moche Period of northern Peru. Using multiple lines of evidence, which include osteological, isotopic and burial context data, this article interprets the human offerings among the Moche of the Andes and argues that the significance of foundation offerings lies not exclusively in the spectacle of sacrifice, but in creating memory that maintains or transforms sacred landscapes.